Engaging rural nurses in the policy development process. Issue 6 (28th October 2016) - Anderson, Judith; Bruce, Brenda; Edwards, Meryn; Podham, Maryanne
Abstract : Background : Reports into neglect by nursing staff have included recommendations to develop policies indicating the fundamental standards of care (Garling, 2008 ; Francis, 2013 ). An area health service in a rural setting in Australia moved to develop such a policy. Objectives : This project was designed to engage nursing staff in a rural health service in the development of a minimum nursing standards policy. Methods : A participatory action research methodology was used to engage with nursing staff. A thematic analysis of focus group meetings was conducted to identify themes. Findings : Though discussions in focus groups did function to develop the policy, participants also expressed views on issues of nursing within the organisation. Themes were identified as either personal or organisational. Personal features included lack of motivation and burnout in staff. Organisational features were controlled by the organisation and included features such as a lack of time and autonomy to commit to the project.